Response inhibition rapidly increases single-neuron responses in the subthalamic nucleus of patients with Parkinson's disease. (November 2016) - Benis, Damien; David, Olivier; Piallat, Brigitte; Kibleur, Astrid; Goetz, Laurent; Bhattacharjee, Manik; Fraix, Valérie; Seigneuret, Eric; Krack, Paul; Chabardès, Stéphan; Bastin, Julien
Abstract: The subthalamic nucleus (STN) plays a critical role during action inhibition, perhaps by acting like a fast brake on the motor system when inappropriate responses have to be rapidly suppressed. However, the mechanisms involving the STN during motor inhibition are still unclear, particularly because of a relative lack of single-cell responses reported in this structure in humans. In this study, we used extracellular microelectrode recordings during deep brain stimulation surgery in patients with Parkinson's disease (PD) to study STN neurophysiological correlates of inhibitory control during a stop signal task. We found two neuronal subpopulations responding either during motor execution (GO units) or during motor inhibition (STOP units). GO units fired selectively before patients' motor responses whereas STOP units fired selectively when patients successfully withheld their move at a latency preceding the duration of the inhibition process. These results provide electrophysiological evidence for the hypothesized role of the STN in current models of response inhibition.